Sensitisation of Student-teachers towards the Direct Teaching of Thinking - Patil, Nalini; Dalvi, Pallavi (JOURNAL OF INDIAN EDUCATION, 2021)
This study attempted to sensitise student-teachers towards the direct teaching of thinking based on Edward De Bono’s CoRT thinking tools. The sample consisted of student-teachers of B.Ed. programmeme. The student-teachers were introduced with the first module of CoRT thinking programme. Five of the student-teachers voluntarily participated further into facilitation of the Direct Teaching of Thinking (DTT) Programme designed to bring in life skills changes for 8th standard students. The paper discusses content understanding of the student-teachers who participated in the sensitisation programme. The data collected in the form of reflections from the student-teachers, is analysed through, the thematic analysis. The analysis revealed that the DTT programme improves communication and interpersonal relations of the student-teachers with their students. The student-teachers felt more confident to use the tools in their subject lesson after the exposure. The thinking programme based on CoRT is relevant not only to be taught in schools but also in teacher education programmes for improvement of teachers’ skills.